Pengaruh Brand Awareness, Influencer Marketing dan Harga Terhadap Keputusan Pembelian pada Produk Sunscreen Nivea di Kota Bandung - Pebriyani, Selvia; Akbar, Ridho Riadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research investigates the impact of brand awareness,influencer marketing and pricing on the purchasing decisions of Nivea Sunscreen products in Bandung City. Employing a quantitative methodology, the study adopts a descriptive and verificative approach. Data was gathered through a questionnaire distributed to 100 participants. The sampling methodutilized is non-probability sampling, specifically purposive sampling, as determined by Slovin’s formula. The target studied consists of individuals who use sunscreen  in Bandung City. Based on hypothesis testing results (t-test), Brand Awareness has a significant and positive impact, indicated by a significance value of 0.000 < 0.05. Influencer Marketing demonstrates a notably positive impact,  evidenced by a significance value of 0.000 < 0.05, and Price has a significant and positive effect with a significance value of 0.000 < 0.05. The hypothesis testing results (f-test) show that the calculated f-value is 380.072 > 2.700, and the significance value is 0.000 < 0.05.Therefore, it can be concluded that Brand Awareness, Influencer Marketing, and Price have a significant and positive influence on Purchasing Decisions.